A família do desastre: representações e lutas no contexto das ações da Fundação Renova entre os povos indígenas Tupinikim de Aracruz – ES - Xavier, Elvis Moreira (2019)
The present dissertation focuses on the social and environmental disaster of Fundão in Mariana – MG that occurred in November 2015, specifically to analyze the family representations around the implementation of the registration, compensation and indemnification program for those affected. Through the Anthropological and Sociological perspective the research is immersed in the community of Caieiras Velha in the city of Aracruz - ES, one of the 12 indigenous villages present in the region of Piraquê-Açu. Utilizing the ethnographic method between the periods of February and September of 2018, each immersion in the field and through it detect sought a constant learning around the research and through this to detect the web of relations present in the community that has a modus operandi that is legitimized by its population in which, through family, parental and community relations, forms a system of symbolic representation, composed of the cacique elected by the community, together with 12 leaders who are responsible for deliberating guidelines regarding community life and which the actions of the Renova Foundation. In this context, it also includes the role of the associations present, focusing on two of them, the AITG and APECI, both with different purposes, but with a lot of influence around the collective discussions. With the interference of external agents in community life, above all, the methodology of applicability of registration and consequently of emergency assistance, tensions and conflicts have tainted the internal relations between families and the community, causing in ruptures in their relations, so that the mobilization in the face of the action of Renova Foundation occurs between the articulation between the Tupinikins families, the leaderships and the cacique, along with the other indigenous villages. The exposed literature will have two thematic axes, the first one to describe the category family to which through the social, spatial, economic and cultural transformations reflected in its composition and gave new narratives and perspectives around its importance and role in the reproduction of human relations. The second axis will work with the conception of disaster carried out by Sociology of Disasters in which this aspect of Social Sciences is focused on measuring and discussing the phenomenon focusing on human aspects and contexts created from human action, whether before, during and after from which disaster is understood not only as a phenomenon of momentary affectation, but as a process of continuous affectation. In addition, the actions of the Renova Foundation and the State in this context will be measured using the technical notes issued by CTOS, a technical chamber belonging to the CIF, the body responsible for regulating the actions of the Renova Foundation, focusing on the implementation of registration, reimbursement and compensation for those affected by the disaster. In order to do so, the implementation of the repair actions occurred in an asymmetrical, time-consuming and distorted way, considering the real dimension of the impacts caused by the rupture of the dam, from which the affected population absorbed the burden of this logic introduced by the Renova Foundation, focusing on indigenous populations, object of this work.